Acute muscle damage as a metabolic response to rapid weight loss in wrestlers - Lukic-Sarkanovic, M.; Roklicer, R.; Trivic, T.; Manojlovic, M.; Gilic, B.; Milovancev, A.; Rossi, C.; Bianco, A.; Carraro, A.; Cvjeticanin, M.; Drid, P. (Biomedical Human Kinetics, 2024)
Study aim: Dietary and non-dietary weight loss methods are highly prevalent among combat sports athletes (CSA). Most CSA undergo rapid weight loss (RWL) usually a week before the competition to reduce their body mass and thus compete in the lowest weight category possible. The objective of the study was to distinguish the impact of high-intensity sport-specific training (HISST) combined with RWL (phase 1 - P1) on muscle damage markers as well as the effects of HISST alone (phase 2 - P2).